Tunable random lasing in dye-doped mesoporous silica SBA-15 - De Vicente, Fábio S. [UNESP]; Moreno, Leandro X. [UNESP]; Prado, Marcus V. A.; Abegão, Luis M. G.; Melo, Leandro A.; Rodrigues, José J.; Alencar, Márcio A. R. C. (American Physical Society (APS), 2021)
Mesoporous silica, known as SBA-15, possesses a hexagonal pore structure, with 8-nm-diameter pores and high surface area (∼700m2/g). The mesoporosity of SBA-15 is excellent to be filled with luminescent chromophores aiming at optical and photonic applications. SBA-15 powder infiltrated with Rhodamine B (RB) was prepared with different RB loads. Using the second harmonic of a pulsed Nd:yttrium aluminum garnet (YAG) laser (8 ns, 10 Hz) as the excitation source, the light emission spectra of the samples were investigated. Typical incoherent feedback random laser behavior was observed. Tunable random laser emissions from 579 to 585 nm were obtained depending on the excitation laser spot diameter and the RB load. The results indicate that mesoporous SBA-15 infiltrated with RB is a promising material for the development of solid-state random lasers.